Sperm immobilization factor of Candida albicans: A proposed mechanism of infertility in female mice - Sareeka Kumari; Aditi Chauhan; Deepali Thaper; Vijay Prabha (Global Journal of Fertility and Research - Peertechz Publications, 2020)
Candida species are the most frequently isolated fungi, responsible for blood stream and urinary tract infections. Various studies have shown Candida albicans to be associated with impediment of sperm parameters. Therefore to determine the underlying mechanism, the standard strain of Candida albicans (MTCC 1637) was employed and it was found to cause complete immobilization of mouse spermatozoa in vitro. Further, sperm immobilization activity was shown by only cell-free supernatant, indicating that the sperm immobilization factor might be released extracellularly, as no activity was observed with the washed cells. The sperm immobilization factor (SIF) from supernatant was precipitated out with ammonium sulphate at the saturation of 60% to 80% and was purified by gel permeation chromatography followed by ion exchange chromatography. The molecular weight of SIF was found to be ~29 kDa. Further, SIF at a concentration of 50µg was capable of causing 100% immobilization of mouse spermatozoa within 30min of incubation at 370C, whereas at 100µg concentration resulted in complete loss of viability. Scanning electron microscopy showed profound morphological alterations with decapitation in mouse spermatozoa after the treatment with SIF. Also, total loss of Mg2+ ATPase activity of mouse spermatozoa was observed at a concentration of 75 and 100µg/ml. Further, in vivo study revealed that the intravaginal application of SIF (10µg) before mating completely avert conception in female mice as no pregnancy related changes were observed in comparison to female mice receiving PBS.